(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
Тhe article considers smart solutions for our contemporary sustainable development. The achievements of nature and physics provide innovative opportunities for changing the economy, creating new jobs and added value, and optimizing the resources used. The entrepreneurial way to do this is the blue economy which uses technological innovations based on the perfection of ecosystems where nothing is lost. The proposed practices along with our environment build sustainable models with the help of which business regains its competitive position.